Pre-monsoon drought variability in the southeastern Loess Plateau over the past 246 years. (10th March 2023) - Duan, Yongkang; Wang, Shuangjuan; Deng, Yang; Gao, Linlin; Qiao, Shuhua; Gou, Xiaohua
Abstract: In recent decades, the Loess Plateau has experienced drying that has had a massive influence on society, ecosystems, and agriculture. However, the limited availability of observed climate data hampers the assessment of continuous drying. In this study, we present a robust tree-ring-width chronology of Chinese Pine with which we reconstructed the pre-monsoon self-calibration Palmer Drought Severity Index (scPDSI) for the last 246 years. The reconstruction is derived from cores sampled from two sites over the southeastern Loess Plateau, is reliable and stable, and explains 54.9% of the variance of observed scPDSI over the period 1957–2017. Our reconstruction reveals obvious annual and decadal variations, with an uneven temporal distribution of dry and wet years. Our reconstruction documents the ongoing drying in recent decades. The period from 2000 to 2018 was the driest over the last 246 years, as according to the 11-year moving average series, five of the top ten most severe droughts occurred during this period. Results of spatial correlation analysis and composite analysis suggest that the North Atlantic sea surface temperature may influence pre-monsoon drought variation over the southeastern Loess Plateau by influencing the westerly jet, the height field, and atmospheric vertical motion.